Understanding & inculcating qualitative audience analysis research in Malaysian screen industry / Hisham Dzakiria, Azilah Kasim and Nuraini Yusoff - Dzakiria, Hisham; Kasim, Azilah; Yusoff, Nuraini (UPENA, 2007)
In the words of Justin Lewis (1991), any screen production power lies in its encounter with the audience. One cannot exist without the other. As he immediately proceeds to acknowledge, however, this idea is "often difficult to grasp empirically" (p. 61) and the issue of how the idea works in practice remains full of methodological confusion and perplexity. This article reviews the contemporary shift and the importance of understanding of audience preferences, perspectives, behaviours, and routines towards the production of films, movies and television production in Malaysia. It proceeds to examine the comparatively underdeveloped state of Malaysian research about screen production audiences, and the variety of incentives to develop such research. The distance between academic and industry research in Malaysia is discussed, and possible explanations of the gap in our academic knowledge of Malaysian screen and film audiences are offered. Finally, the article considers possible means to approach the meaningful study of the media reception process within Malaysian audiences or viewers. The audience profile is considered as a key factor for programming of screen production. Understanding audience and their preferences could sustain continuous programming and development of new production. This article advocated the need for the professionals in the industry to inculcate such understanding and call for more qualitative research into audience analysis for sustainable development of the industry in this country.